A global spatially explicit database of changes in island palaeo‐area and archipelago configuration during the late Quaternary. Issue 5 (5th February 2018) - Norder, Sietze J.; Baumgartner, John B.; Borges, Paulo A. V.; Hengl, Tomislav; Kissling, W. Daniel; van Loon, E. Emiel; Rijsdijk, Kenneth F.
Abstract: Motivation: Past sea level fluctuations have shaped island area and archipelago configuration. The availability of global high‐resolution data on bathymetry and past sea levels allows reconstruction of island palaeo‐geography. Studies on the role of palaeo‐area often consider only the Last Glacial Maximum, which neglects the dynamics of island fusion and fission resulting from cyclic sea level fluctuations throughout the Quaternary. Currently, no global database is available to test the role of changing island geographies driven by Quaternary sea level change on evolutionary, ecological and archaeological patterns. However, data on island palaeo‐environments is crucial for understanding insular biodiversity distributions and human settlement patterns. Here, we present the Palaeo‐Islands and Archipelago Configuration (PIAC) database, containing sea level‐driven palaeo‐geography changes over the late Quaternary of 178 islands in 27 archipelagos, and discuss its relevance, limitations and uncertainties. The R functions developed to create the PIAC database are provided to allow calculations for other islands, time steps, sea‐level curves and higher spatio‐temporal resolutions. Main types of variables contained: Polygon shapefiles with archipelago configuration and tables with palaeo‐area per island. Spatial location and grain: The database has a global representation, with 27 archipelagos being covered: Aldabra, Azores, Balearic Islands, California Channel Islands, Canary Islands, Cape Verde, Comoros, Cook Islands, Crozet Islands, Dutch Caribbean, Galápagos, Gulf of Guinea, Hawaii, Inner Seychelles, Juan Fernández, Kuril Islands, Madeira, Marianas, Marquesas, Mascarenes, Phoenix Islands, Pitcairn Islands, Prince Edward Islands, Revillagigedo, Samoan Islands, Society Islands and Tristan da Cunha. All data are at 1 km 2 spatial resolution. Time period and grain: The focus of this paper is on the last 35 kyr; data for the last 140 kyr are also provided. The grain is 1 kyr temporal resolution. Level of measurement: Data are per island, grouped per archipelago. Software format: The data were produced in the R programming language.